2012
DOI: 10.1186/1471-2407-12-77
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring physical and psychosocial symptom trajectories in ovarian cancer patients receiving chemotherapy

Abstract: BackgroundDiagnosis and treatment of ovarian cancer (OC) entail severe symptom burden and a significant loss of quality of life (QOL). Somatic and psychological impairments may persist well beyond active therapy. Although essential for optimal symptom management as well as for the interpretation of treatment outcomes, knowledge on the course of QOL-related issues is scarce. This study aimed at assessing the course of depressive symptoms, anxiety, fatigue and QOL in patients with OC over the course of chemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
43
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 52 publications
7
43
0
2
Order By: Relevance
“…Nevertheless, this study also confirmed that the QoL improves with ongoing treatment and continues to get better after the end of CT, reaching a level similar to that of the general female population [17,18]. The authors underlined the importance of longitudinal assessment of QoL in order to facilitate the identification of symptom burden in EOC patients.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Nevertheless, this study also confirmed that the QoL improves with ongoing treatment and continues to get better after the end of CT, reaching a level similar to that of the general female population [17,18]. The authors underlined the importance of longitudinal assessment of QoL in order to facilitate the identification of symptom burden in EOC patients.…”
Section: Discussionsupporting
confidence: 61%
“…Unfortunately, very few authors have studied this topic before, but as previously shown by Meraner et al [17], there is a significant deterioration in QoL during CT, especially at the beginning of the treatment and immediately after the first cytoreductive surgery. Nevertheless, this study also confirmed that the QoL improves with ongoing treatment and continues to get better after the end of CT, reaching a level similar to that of the general female population [17,18].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…В данной работе определено, что бо льшая часть пациенток, страдающих онкологическими заболева-ниями, испытывают дистресс, тревогу и депрессию субклинического уровня, что было показано и в ранее проведенных исследованиях [12]. Так, известно, что сам факт постановки диагноза онкологического заболевания является сильным психотравмирующим фактором [13].…”
Section: результатыunclassified
“…6,7 Most symptom prevalence studies are cross-sectional offering only a snapshot of the cancer experience often conducted among heterogeneous groups of patients with gynecological cancer. 2,3,8Y10 Longitudinal studies on symptoms during and after treatment for ovarian cancer have examined symptom persistence and associated symptom burden over time, but the focus has mainly been on a narrow set of symptoms, 11,12 and as we know that symptoms affect each other negatively, this limits the understanding of symptom burden. 13 Therefore, the purpose of this study was to investigate occurrence of multiple symptoms in patients with ovarian cancer before, during, and 6 months after start of chemotherapy.…”
mentioning
confidence: 99%